A clinical study of impact of anaemia in pregnancy on maternal and neonatal outcome - K., Lokeshwari; Arpana, Anju; Mudigubba, Manoj Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim is to study effect of anaemia in obstetrics patients during antepartum, intrapartum and postpartum and to find the incidence of maternal and neonatal morbidity and mortality in those patients. Methods: A prospective clinical study was conducted on patients receiving obstetric care at Basaveshwara Medical College and Hospital from July 2016 to July 2018.Pregnant women with Hb less than 8g were included in the study to determine the outcome of pregnancy in severe anaemia and determine the causes of anaemia. Acute cases of obstetrical haemorrhages as in antepartum and postpartum haemorrhages and all medical and surgical high-risk factors except anaemia, were excluded from the study. Results: A total of 200 pregnant anaemic patients with haemoglobin less than 8g/dl were included in the study. The patients were divided into two groups based on haemoglobin concentration at first presentation. Patients with haemoglobin level less than 5g/dl were included in group A (N=44, 22%), and rest of the patients were included in group B (N=156, 78%). Most commonly observed complications in the study were preeclampsia and eclampsia (46 cases), preterm labour (46 cases) and IUGR (30 cases). In both group of patients, the commonest cause of anaemia in pregnancy was iron deficiency. The greater the severity of anaemia in pregnancy, greater was the risk of preeclampsia, preterm delivery, low birth weight and stillbirth. Conclusions: This study reveals that severe anaemia which is commonly observed in the pregnancy in our country, gives rise to maternal and perinatal morbidities and mortalities.